Does perceived quality mediate the effect of generation Z’s consumer ethnocentrism on local sneakers purchase intention? - Dhewi, Titis Shinta; Oktaviani, Rosana (Universitas Negeri Surabaya, Indonesia, 2023)
Understanding consumer ethnocentrism will enhance the tendency of individuals to have higher purchase intentions for local products. This research examines the direct effect of consumer ethnocentrism on the purchase intention of local sneakers in Indonesia and determine whether perceived quality can mediate the influence of consumer ethnocentrism on the purchase intentions of local sneakers. This research uses explanatory approach with respondents about 260 Generation Z in Indonesia. The data was analysed by Partial Least Square (PLS) with the WarpPLS 4.0 software. This research reveals that consumer ethnocentrism has a positive and significant influence on purchase intention, then perceived quality positively drives purchase intention. Additionally, the result shows that consumer ethnocentrism positively and significantly affects the perceived quality of local sneakers. Lastly, perceived quality can mediate the nexus between purchase intention on the perceived quality of local sneakers in Indonesia. This study provides managerial implication for companies that produce local sneakers should focus on improving the perceived quality of their products to increase purchase intention among consumers with high levels of ethnocentrism.